About some problems of viktimologichesky prevention of crime. (Journal of actual problems of jurisprudence, 2016)
In this article the concept of a viktimologiya, as about the doctrine about victims is given. Problems of viktimologichesky prevention are considered. Analyzing levels of viktimologichesky prevention, the author offered recommendations about decrease and crime rate neutralization.
Keywords: viktimologiya; viktimologichesky prevention; victim; viktimnost; crime